Evaluasi Pembelajaran Bahasa Arab di Sekolah MTS Ali Imron Bandar Selamat: Evaluation of Arabic Language Learning at MTS Ali Imron Bandar Selamat School - Nurhayati Nurhayati; Usiono Usiono (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to evaluate the implementation of Arabic language learning at MTs Ali Imron Bandar Selamat School using a case study approach. The main focus of this study is to identify the effectiveness of the teaching methods applied, as well as to determine the obstacles faced by teachers and students in the learning process. This study was conducted using qualitative research methods and a case study approach. Data were collected through classroom observations, interviews with teachers and students, and documentation related to learning activities. Furthermore, the researcher will analyze the data and test its validity. The results of the study indicate that although there have been significant efforts in implementing communication methods and contextual approaches, there are still several challenges that hinder the success of Arabic language learning. These challenges include limited learning facilities, lack of student motivation, and limited time available to study Arabic material thoroughly. Based on these findings, it is recommended that learning facilities be improved, further training for teachers, and the development of a curriculum that is more in accordance with student needs. This study is expected to contribute to the development of the quality of Arabic language learning at MTs Ali Imron Bandar Selamat and similar schools.